2010
DOI: 10.1007/s12298-010-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic fidelity of micropropagated date palm (Phoenix dactylifera L.) plants by RAPD and ISSR markers assay

Abstract: RAPD (Random Amplified Polymorphic DNA) and ISSR (Inter-Simple Sequence Repeats) markers assay were employed to validate the genetic stability of date palm (Phoenix dactylifera L.) plants multiplied through somatic embryogenesis with upto forty two in vitro subcultures. Out of the 160 RAPD and 21 ISSR primers screened, 30 RAPD and 12 ISSR primers produced a total of 347 (246 RAPDs + 101 ISSRs) clear, distinct and reproducible amplicons, which were monomorphic across all micropropagated plants (27) studied. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 21 publications
4
17
0
Order By: Relevance
“…RAPD has been successfully applied in genetic variation investigations of Mucuna pruriens due to its usefulness as an informative and cheap tool for plant breeding programs (Patil et al 2016). There are also many researchers using these markers as one of their techniques to study the genetic diversity of their desired plant species (Desai et al 2015;Kumar et al 2009Kumar et al , 2010Mei et al 2015;Patel et al 2015;Patil et al 2016;Pu et al 2009;Saleh 2015;Zhao et al 2013;Zhao et al 2015). RAPD and ISSR are dominant markers that function well in DNA fingerprinting studies of plant species.…”
Section: Introductionmentioning
confidence: 99%
“…RAPD has been successfully applied in genetic variation investigations of Mucuna pruriens due to its usefulness as an informative and cheap tool for plant breeding programs (Patil et al 2016). There are also many researchers using these markers as one of their techniques to study the genetic diversity of their desired plant species (Desai et al 2015;Kumar et al 2009Kumar et al , 2010Mei et al 2015;Patel et al 2015;Patil et al 2016;Pu et al 2009;Saleh 2015;Zhao et al 2013;Zhao et al 2015). RAPD and ISSR are dominant markers that function well in DNA fingerprinting studies of plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular marker techniques like Random Amplified Polymorphic DNA (RAPD) and Inter Simple Sequence Repeats (ISSR) are rapid, sensitive and reliable in analysis of genetic stability of in vitro regenerants. These two marker systems have been successfully applied to detect the somaclonal variations in a number of species such as Cymbopogon martini (Bhattacharya et al 2010), Phoenix dactylifera (Kumar et al 2010) and Simmondsia chinensis (Kumar et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…In commercial micropropagation it is very important to test the genetic conformity/true-to-type of the regenerated plants. Several researchers have used molecular markers (AFLP, ISSR and RAPD) to confirm the genetic conformity of the tissue-cultured plants (Kumar et al, 2010;Othmani et al, 2009cOthmani et al, , 2010. The use of RAPD primers showed micropropagated date cv.…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Barhee and Khalas which display dwarfism and abnormal flower development (Al-Kaabi;Zaid;Ainsworth, 2007;Zaid;Al-Kaabi, 2003). Kumar et al (2010) evaluated 27 micropropagated date plants with 160 RAPD and 21 ISSR primers, in which 30 RAPD and 12 ISSR primers produced a total of 347 reproducible monomorphic band; the results suggested that the micropropagated plants are true-to-type. Aslam, Khan and Naqvi (2015) established the somatic embryo derived regeneration protocol for the six cvs.…”
Section: Molecular Characterizationmentioning
confidence: 99%